Implementation and Impact of Environmentally Sound Schools and Adiwiyata Program in East Java Province: A Literature Review - Siti Aqilah; Suci Siti Lathifah (CV. Dharma Samakta Edukhatulistiwa, 2023)
The purpose of this data gathering endeavor is to discern and scrutinize empirical research works that have been published in academic journals from 2010 onwards, with a specific emphasis on the execution of ecologically sustainable schools in the East Java Province. The review incorporates a range of research methodologies, including quantitative, qualitative, mixed methods, and literature review studies. The Sinta database, which is a Science and Technology Index, is employed for the purpose of conducting literature research. Through the examination of various articles, it has been determined that the introduction of ecologically sustainable schools in the region of East Java has yielded favorable results. Educational institutions have developed all-encompassing initiatives that prioritize ecological factors to cultivate and augment ecological consciousness among their constituents. The aforementioned programs comprise a range of endeavors, including but not limited to waste management, energy efficiency, preservation of biodiversity, and implementation of sustainable practices. The results emphasize the importance of the school's function and the proactive engagement of the school community in achieving an ecologically sustainable educational institution. The present literature review offers significant perspectives on the execution of ecologically sustainable schools in East Java Province and underscores the significance of incorporating environmental principles and practices into the educational milieu. The aforementioned serves as a fundamental basis for prospective investigations and bolsters the continuous endeavors towards establishing ecologically aware educational institutions that foster sustainable progress within the area.